Anatomical Evidence for a Direct Projection from Purkinje Cells in the Mouse Cerebellar Vermis to Medial Parabrachial Nucleus - Hashimoto, Mitsuhiro; Yamanaka, Akihiro; Kato, Shigeki; Tanifuji, Manabu; Kobayashi, Kazuto; Yaginuma, Hiroyuki (Frontiers in Neural Circuits, 2018)
Cerebellar malformations cause changes to the sleep-wake cycle, resulting in sleep disturbance. However, it is unclear how the cerebellum contributes to the sleep-wake cycle. To examine the neural connections between the cerebellum and the nuclei involved in the sleep-wake cycle, we investigated the axonal projections of Purkinje cells in the mouse posterior vermis by using an adeno-associated virus (AAV) vector (serotype rh10) as an anterograde tracer. When an AAV vector expressing humanized renilla green fluorescent protein (hrGFP) was injected into the cerebellar lobule IX, hrGFP and synaptophysin double-positive axonal terminals were observed in the region of medial parabrachial nucleus (MPB). The MPB is involved in the phase transition from rapid eye movement (REM) sleep to non-REM sleep and vice versa, and the cardiovascular and respiratory responses. The hrGFP-positive axons from lobule IX went through the ventral spinocerebellar tract and finally reached the MPB. By contrast, when the AAV vector was injected into cerebellar lobule VI, no hrGFP-positive axons were observed in the MPB. To examine neurons projecting to the MPB, we unilaterally injected Fast Blue and AAV vector (retrograde serotype, rAAV2-retro) as retrograde tracers into the MPB. The cerebellar Purkinje cells in lobules VIII–X on the ipsilateral side of the Fast Blue-injected MPB were retrogradely labeled by Fast Blue and AAV vector (retrograde serotype), but no retrograde-labeled Purkinje cells were observed in lobules VI–VII and the cerebellar hemispheres. These results indicated that Purkinje cells in lobules VIII–X directly project their axons to the ipsilateral MPB but not lobules VI–VII. The direct connection between lobules VIII–X and the MPB suggests that the cerebellum participates in the neural network controlling the sleep-wake cycle, and cardiovascular and respiratory responses, by modulating the physiological function of the MPB.